Peruvian-oriental culinary business plan proposal - San Juan Rugel, Genny Lucylaura (2020)
The world is constantly changing and with it, the lifestyles of consumers. As these changes take place, new lifestyles are born causing business models to adapt and innovate. In this new context, there are consumers that highly care about their health, the quality product they consume, future consequences of their diet and have high expectations of their preferable food companies. Wok & Well was born from this new lifestyle and customer mindset, providing a culinary service aimed to keep a healthier life without leaving out customer´s tastes and customs. Wok & Well offers Peruvian-Oriental fusion food in wok and emphasizes on providing more beneficial and high quality options, as well as giving our customers 100% free will on what to eat and how to eat it from a pool of healthy ingredients followed by 4 simple steps.